Research of Heat and Mass Transfer Processes in the Nodes of Free-Flow Micro-Hpp With the Use of 3D Technology; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Yankovsky S. A. Stanislav Aleksandrovich (2016, 2016)
Title screen